2023
DOI: 10.1021/acs.analchem.2c04714
|View full text |Cite
|
Sign up to set email alerts
|

Zn2+-Induced Gold Cluster Aggregation Enhanced Electrochemiluminescence for Ultrasensitive Detection of MicroRNA-21

Abstract: Herein, Zn 2+ -induced gold cluster aggregation (Zn 2+ -GCA) as a high-efficiency electrochemiluminescence (ECL) emitter is first employed to construct an ECL biosensor to ultrasensitively detect microRNA-21 (miRNA-21). Impressively, Zn 2+ not only can induce the aggregation of monodispersed gold clusters (Au NCs) to limit the ligand vibration of Au NCs for improving ECL emission but also can be utilized as a coreaction accelerator to catalyze the dissociation of coreactant S 2 O 8 2− into sulfate radicals (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Notably, chiral ferrocene (Fc) derivatives may undergo a reversible redox reaction between ferricinium cation species (Fc + ) and ferrous, and they can act as suitable enantioselective sensors for chiral electroanalysis. , Moreover, Fc and its derivatives can function as classical quenchers in electrochemiluminescence (ECL) systems due to their high stability and high quenching efficiency. For example, Fc can completely quench the ECL signal of the [Ru­(bpy) 3 ] 2+ /TPrA (tripropylamine) system, the cathodic ECL of CdTe quantum dots, and the ECL of the O 2 /S 2 O 8 2– system. Interestingly, Fc can catalyze the decomposition of H 2 O 2 to generate oxygen-related free radicals, leading to the improved ECL signal in luminol (or luminol derivatives)–H 2 O 2 systems. Until now, there is no research about the production of an improved ECL signal, with Fc as a coreaction accelerator for other ECL luminophors in dissolved O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, chiral ferrocene (Fc) derivatives may undergo a reversible redox reaction between ferricinium cation species (Fc + ) and ferrous, and they can act as suitable enantioselective sensors for chiral electroanalysis. , Moreover, Fc and its derivatives can function as classical quenchers in electrochemiluminescence (ECL) systems due to their high stability and high quenching efficiency. For example, Fc can completely quench the ECL signal of the [Ru­(bpy) 3 ] 2+ /TPrA (tripropylamine) system, the cathodic ECL of CdTe quantum dots, and the ECL of the O 2 /S 2 O 8 2– system. Interestingly, Fc can catalyze the decomposition of H 2 O 2 to generate oxygen-related free radicals, leading to the improved ECL signal in luminol (or luminol derivatives)–H 2 O 2 systems. Until now, there is no research about the production of an improved ECL signal, with Fc as a coreaction accelerator for other ECL luminophors in dissolved O 2 .…”
Section: Introductionmentioning
confidence: 99%
“… In addition, the ECL efficiency of Pdots was calculated to be 5.85%, which is 32-fold higher than that of CMP (i.e., 0.18%) and much higher than those of the as-reported literature (Table S1). , Therefore, these results indicated that as-prepared AIE-activated Pdots could serve as excellent ECL nanoemitters.…”
Section: Resultsmentioning
confidence: 99%
“…Gold nanoclusters (Au NCs) have recently raised considerable concern owing to their inherent outstanding biocompatibility, excellent photostability, and easy-to-functional regulation. Nevertheless, the Au NCs still suffer from inferior ECL efficiency in aqueous media, limiting their advanced applications. More recently, up-to-date strategies of using co-reaction accelerators, , using electrosensitizers, engineering the valence state, , tuning the ligand function, host–guest recognition, , and aggregation-induced ECL, have been reported in succession to prepare high-efficient ECL Au NCs through accelerating the charge transfer process for efficient collision/reactions or reducing the nonradiative transition of excited states. Even with the great progress, nevertheless, these external strategies require the addition of functional exogenous materials to construct a Au NCs-based ternary/binary system, which requires complicated operation procedures, is time-consuming, and is susceptible to exogenous factors, reducing the simplicity and reproducibility of the ECL bioassay.…”
Section: Introductionmentioning
confidence: 99%